Classification approach to the assessment of factors determining the value of an enterprise in the strategic management system - O. M. Dzhavadova; I. V. Kapinosov (Вестник Северо-Кавказского федерального университета, 2023)
The aim of the study is to find approaches to assess the actual value of modern enterprises in order to increase the level of their objective assessment and the possibility of building effective strategic management. The materials and methods underlying the work are based on fundamental methods of searching for economic phenomena occurring at various levels, including the level of an economic entity. The main results of the study reflect the presented main groups of factors and primary elements that determine the commercial value of the enterprise. Conclusions and rationale for the novelty of the work: the study based on various methods adapted to modern conditions allows drawing a conclusion about the need for a systematic approach to assessing the value of enterprises in a changing market environment. The novelty of the work lies in the development of methodological approaches in assessing the value of a modern enterprise, taking into account the variety of external and internal factors that affect a successful operation of an economic entity.